Assessment of genetically modified oilseed rape MON 88302 for renewal authorisation under Regulation (EC) No 1829/2003 (dossier GMFF‐2023‐21220) - EFSA Panel on Genetically Modified Organisms (GMO); Josep Casacuberta; Francisco Barro; Albert Braeuning; Ruud deMaagd; Michelle M. Epstein; Thomas Frenzel; Jean‐Luc Gallois; Frits Koning; Antoine Messéan; F. Javier Moreno; Fabien Nogué; et al. (EFSA Journal)
Abstract Following the submission of dossier GMFF‐2023‐21220 under Regulation (EC) No 1829/2003 from Bayer CropScience LP, the Panel on Genetically Modified Organisms of the European Food Safety Authority was asked to deliver a scientific risk assessment on the data submitted in the context of the renewal of authorisation application for the herbicide‐tolerant genetically modified oilseed rape MON 88302, for food and feed uses, excluding cultivation within the European Union. The data received in the context of this renewal application contained post‐market environmental monitoring reports, an evaluation of the literature retrieved by a scoping review, a search for additional studies performed by or on behalf of the applicant and updated bioinformatics analyses. The GMO Panel assessed these data for possible new hazards, modified exposure or new scientific uncertainties identified during the authorisation period and not previously assessed in the context of the original application. Under the assumption that the DNA sequence of the event in oilseed rape MON 88302 considered for renewal is identical to the sequence of the originally assessed event, the GMO Panel concludes that there is no evidence in renewal dossier GMFF‐2023‐21220 for new hazards, modified exposure or scientific uncertainties that would change the conclusions of the original risk assessment on oilseed rape MON 88302.